Qian Yang Yu Yin Granule Improves Renal Injury of Hypertension by Regulating Metabolic Reprogramming Mediated by HIF-1α/PKM2 Positive Feedback Loop - Qian, Lichao; Ren, Shuai; Xu, Zhongchi; Zheng, Yawei; Wu, Lihua; Yang, Ying; Wang, Yixuan; Li, Jie; Yan, Shihai; Fang, Zhuyuan (Frontiers in Pharmacology, 2021)
Protection against hypoxia injury is an important therapeutic strategy for treating hypertensive nephropathy. In this study, the effects of Qian yang yu yin granule (QYYY) on spontaneously hypertensive rats fed with high salt diet and HEK293T cells exposed to hypoxia were investigated. After eight weeks’ treatment of QYYY, blood pressure, serum creatinine, serum cystatin C, blood urea nitrogen, urinary β2-microglobulin, urinary N-acetyl-β-glucosaminidase and urinary microalbumin were assessed. The changes of hypoxia-inducible factor-1α (HIF-1α), pyruvate kinase M2 (PKM2), glucose transport 1 (GLUT1), lactate dehydrogenase A (LDH-A), connective tissue growth factor (CTGF), transforming growth factor-β1 (TGF-β1), ATP, lactate, pyruvate and pathology were also assessed in vivo. HEK293T cells pre-treated with QYYY and/or HIF-1α over expressing cells were cultured in a three gas hypoxic incubator chamber (5% CO2, 1% O2, 94% N2) for 12 hours and then the expressions of HIF-1α, PKM2, GLUT1, LDH-A, CTGF, TGF-β1, ATP, lactate and pyruvate were detected. Our results showed that QYYY promoted the indicators of renal inflammation and fibrosis mediated by HIF-1α/PKM2 positive feedback loop in vivo and vitro. Our findings indicated that QYYY treated hypertensive nephropathy by regulating metabolic reprogramming mediated by HIF-1α/PKM2 positive feedback loop.